Dialogue of students during the creation of projects with Scratch in Mathematics classes - Bitencourt, Agner Lopes; Fioreze, Leandra Anversa (Revista Internacional de Pesquisa em Educação Matemática, 2024)
The research aims to verify and understand how dialogue occurs in the construction of projects via Scratch programming in mathematics classes based on dialogic acts and theoretical elements. The empirical material included computer recordings from three groups of two eighth grade classes. The recordings show audio from programs, acts, voices and images of students, and were transcribed for analysis of messages that means dialogue. The results show the occurrence of dialogue during interactions characterized by joint work, mutual help, search for consensus, respect for others, being separate and connected. When creating projects in Scratch, it was necessary to challenge themselves, testing possibilities, dealing with the unpredictability of an investigation, so it is necessary to understand perspectives from both sides, position themselves and argue, that is, pedagogical practice has characteristics dialogical in order to build group behaviors related to dialogical processes and theoretical elements.